Creating worlds for my music to exist: How women composers of electroacoustic music make place for their voices - McCartney, Andra (Université York, 1994)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
https://ocul-yor.primo.exlibrisgroup.com/permalink/01OCUL_YOR/j50f41/cdi_proquest_journals_304118103 Accès par ProQuest
Keywords: 1900-1999; 1990-1999; DIG; amériques; arts; canada; discipline; femmes* artistes; genre; montréal; musique; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; toronto; vancouver

Choral, public and private listener responses to Hildegard Westerkamp's École Polytechnique - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; arts; canada; cyborg; deuil; discipline; femmes* artistes; guérison; musique; mémoire; polytechnique; périodes historiques; ressource en ligne; régions géographiques; thématiques; trauma; violences; violences contre les femmes*; violences sexistes; émotions

Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
https://spectrum.library.concordia.ca/id/eprint/977861/1/Madden_PhD_F2013.pdf
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail